Fundamental Sentential Level Issues of English Information Structure - Tuấn, Huỳnh Anh (VNU Journal of Foreign Studies, 2013)
Abstract: This paper is an exploration into the fundamental sentential level issues of English information structure: the order in which information is distributed within the sentence, the given/new status of the information exchanged, the contextual constraints on the given/new status, and the syntactical devices used to indicate this given/new status. The conclusion that these issues are fundamental to sentential level English information structure is based on the studies of Birner and Ward (1998), Ward and Birner (2001), Halliday and Matthiessen (2004), Erteschik-Shir (2007), and others. The perspective from which these issues are viewed in the paper adopts Quirk et al. (1985)’s comprehensive approach in which a linguistic construction is discussed with regard to its syntactic features in relation to its pragmatic function under contextual constraints. At the discourse level, these issues can be discussed within Winter (1994)’s clause-relational approach to text analysis in which the clause is viewed as a device of co-relevance constructing and distributing information. Given and new information status, information distribution, information distribution signals and contextual constraints are embedded in the relations held among the clauses which can be interlocked to create the logical structure of the whole text. However, discourse level information structure does not fall within the scope of this paper.Keywords: Information structure, information distribution, given/new status, contextual constraints, syntactical devices, non-canonical constructions.